An ion‐paired moxifloxacin nanosuspension eye drop provides improved prevention and treatment of ocular infection. Issue 3 (22nd June 2021) - Josyula, Aditya; Omiadze, Revaz; Parikh, Kunal; Kanvinde, Pranjali; Appell, Matthew B.; Patel, Pratikkumar; Saeed, Hiwa; Sutar, Yogesh; Anders, Nicole; He, Ping; McDonnell, Peter J.; Hanes, Justin; et al.
Abstract: There are numerous barriers to achieving effective intraocular drug administration, including the mucus layer protecting the ocular surface. For this reason, antibiotic eye drops must be used multiple times per day to prevent and treat ocular infections. Frequent eye drop use is inconvenient for patients, and lack of adherence to prescribed dosing regimens limits treatment efficacy and contributes to antibiotic resistance. Here, we describe an ion‐pairing approach used to create an insoluble moxifloxacin–pamoate (MOX–PAM) complex for formulation into mucus‐penetrating nanosuspension eye drops (MOX–PAM NS). The MOX–PAM NS provided a significant increase in ocular drug absorption, as measured by the area under the curve in cornea tissue and aqueous humor, compared to Vigamox in healthy rats. Prophylactic and treatment efficacy were evaluated in a rat model of ocular Staphylococcus aureus infection. A single drop of MOX–PAM NS was more effective than Vigamox, and completely prevented infection. Once a day dosing with MOX–PAM NS was similar, if not more effective, than three times a day dosing with Vigamox for treating S. aureus infection. The MOX–PAM NS provided increased intraocular antibiotic absorption and improved prevention and treatment of ocular keratitis, and the formulation approach is highly translational and clinically relevant.